2021
DOI: 10.3390/rs13020218
|View full text |Cite
|
Sign up to set email alerts
|

Random Forest Regression Model for Estimation of the Growing Stock Volumes in Georgia, USA, Using Dense Landsat Time Series and FIA Dataset

Abstract: The forest volumes are essential as they are directly related to the economic and environmental values of the forests. Satellite-based forest volume estimation was first developed in the 1990s, and the accuracy of the estimation has been improved over time. One of the satellite-based forest volume estimation issues is that it tends to overestimate the large volume class and underestimate the small volume class. Free availability of the major satellite imagery and the development of cloud-based computational pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The simplest approaches are based on multispectral analysis of freely-available VNIR imagery having a spatial resolution of the order of 10 m or coarser [11][12][13][14][15][16][17]. Useful enrichment of the available feature space has been demonstrated using multitemporal datasets [18][19][20][21], incorporating texture measures [14,22] and field-derived or satellite-derived three-dimensional information [23][24][25][26][27][28][29][30]. Other approaches are based on the use of ultra-high-resolution VNIR imagery (usually not free of cost) [31,32], radar imagery [1,[33][34][35][36][37][38][39][40][41][42][43][44][45][46], or combinations of VNIR and radar imagery [47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…The simplest approaches are based on multispectral analysis of freely-available VNIR imagery having a spatial resolution of the order of 10 m or coarser [11][12][13][14][15][16][17]. Useful enrichment of the available feature space has been demonstrated using multitemporal datasets [18][19][20][21], incorporating texture measures [14,22] and field-derived or satellite-derived three-dimensional information [23][24][25][26][27][28][29][30]. Other approaches are based on the use of ultra-high-resolution VNIR imagery (usually not free of cost) [31,32], radar imagery [1,[33][34][35][36][37][38][39][40][41][42][43][44][45][46], or combinations of VNIR and radar imagery [47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that RF can be used to integrate spectrum data into regression investigations, sometimes producing better results than conventional regression techniques (Dos Reis et al, 2018). For data-based predictions, such as forest attribute estimation, RF regression is frequently utilized (Obata et al, 2021). The ability of an RF model to assess a variable's importance-that is, the degree to which each feature variable contributes to the model's prediction-is one of its main benefits (Obata et al, 2021).…”
Section: Random Forest (Rf)mentioning
confidence: 99%
“…The random forest technique can also process big data with thousands of variables. A class can automatically balance datasets when data is less sparse than other classes [23].…”
Section: Random Forest (Rf) Regressionmentioning
confidence: 99%